The study of Spirobranchus (christmas worms) based on substrate in Lamteung waters of Pulo Aceh, Aceh Besar District. Issue 1 (February 2021) - Mursawal, A; Sarong, M A; Irham, M; Hermi, R
Abstract: The objective of this paper is to analyze the number of Spirobranchus (Christmas worms) based on body color in the waters of Lamteung, Pulo Aceh District, Aceh Besar District, Aceh Province and to examine the substrate dominated by individual Spirobranchus in Lamteung waters of Pulo Aceh, Aceh Besar District, Aceh Province. The research activity was carried out in December 2018. The research area was determined by purposive sampling. Areas with Christmas worms were divided into three stations based on the substrate, namely station 1 with a massive coral substrate, station 2 with branched coral substrate, and station 3 with a substrate other than the two. Data were collected by documenting individuals based on color, coral substrate, and coral species occupied by Spirobranchus . The presence of Spirobranchus and its body color were analyzed descriptively. The results obtained were number of Spirobranchus based on body color found in Lamteung waters which occupied a Coral Massive were 13 individuals and occupied the Acropora Digitate were one individu. The dominance index obtained on the Coral Massive substrate was 0.86 and on the Acropora digitate substrate was 0.01. The conclusions obtained that Spirobranchus based on body color which occupies more individuals on the Coral Massive substrate, when compared to Acropora digitate subtrate. Coral Massive substrate type has a high degree of dominance compared to Acropora digitate substrate.